The Capital Market Reaction To The Corona Covid-19 Virus Outbreak Events: Reaksi Pasar Modal Terhadap Peristiwa Wabah Virus Corona Covid-19 - Wardah Azizah; Nurasik (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to get a real picture of the Capital Market Reaction to the Corona Covid-19 Virus Outbreak (Study on LQ-45 Companies Listed on the Indonesia Stock Exchange). The analytical tool used is descriptive statistical analysis and classical assumption test. To test the hypothesis, it is done using data analysis in the form of Paired Sample T-Test using the statistical program